Buccal habits in deaf and hypoacusis patients at the Playa municipality, Havana, 2011-2014 - Yuneisy Santos Pérez; Aurora Novoa López (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction:In the ancient times the deaf were consider beings with defects that should be sacrificed for the humanity's welfare; if they lived they were considered idiots by not possessing articulate language. Nowadays deaf people issues are studied from the different areas of health and education. Objective: To identify the behavior of the buccal habits in deaf and hypoacusis patients. Material and Method: It was carried out a descriptive study of traverse court, with a population of 20 people deaf and hypoacusis, with ages between 15 and 60 or more years old, of both sexes, belonging to the Cuban Deaf National Association of the Beach Municipality in Havana, in the period 2011-2014. It was carried out survey, buccal exams and search of information on the topic. The obtained data were processed, Tables were made to facilitate the interpretation of them and the results were given by percent. Results: The feminine sex was the one of more prevalence with a 45.0% between 20-59 years old. The ingestion of solid sugary foods among the foods, the onychophag practice and the consumption of coffee represented a 35.0% in same group of ages. 45.0% of studied patients carry out the dental brushing in a mixed way, twice a day and with little use of the dental thread. Conclusions: More than a half of the studied population it ingests solids sugary foods among the foods, they consume coffee, they practice the onychophagia and carry out the dental brushing in an incorrect way. Keywords:Buccal habits, deaf, dietetic habits, toxic habits, buccal hygienic, occupational habits, hypoacusis.